IMPLEMENTASI METODE PERHITUNGAN MARGIN PADA AKAD PEMBIAYAAN MURABAHAH BMT UGT SIDOGI - HAYATUL MILLAH; NUR HAYATI (Institut Bisnis Muhammadiyah Bekasi, 2021)
This study aims to determine the implementation of the margin calculation method on murabahah financing contracts at BMT UGT Sidogiri Capem Semampir Kraksaan Probolinggo. This type of research is a qualitative research. Qualitative method is a research method that uses the philosophy of positivism as a basis, this method is used to conduct research in conditions of natural objects. This study shows the results that the percentage margin for murabahah financing is determined by the size of the financing ceiling proposed by each customer, at BMT UGT Sidogiri Capem Semampir Kraksaan Probolinggo, the maximum ceiling in accordance with the policy of the Islamic Bank central team is only 50,000,000 . BMT UGT Sidogiri Capem Semampir Kraksaan Probolinggo in calculating the profit margin for murabahah financing using the principal calculation method, which is a simple formula used by BMT to determine the total installments, principal financing and profit margins.